Lectura de imágenes y su relación con el desarrollo de capacidades en los niños/as de 5 años en el área de comunicación en la I.E N°089 de la ciudad de Rioja - Limo Del Aguila, Diana Sofía (2016)
This research: Reading images and their relationship with the capacity of children of 5 years in the commünications area of School No. 089 in the city of Rioja, 2015, aims to determine the relationship between image reading with capacity development in children of 5 years in the area of communication in the School No. 089 in the city of Rioja, 2015. the specific objectives were to analyze the level of development capacities of children of 5 years in the area of communication, analyze the level of image reading in children of 5 years ·in the area of communication and establish the relationship between image reading with capacity building in children aged 5 years in the area of communication. Reading images is based on the theoretical foundations of Lomas (1997), Zamora (2000), Pablos (2009), Garcia (2001), Galdos (1989), Joly (1999), Manayay (2004), which presented as a dexterity understand the messages; and capacity building in Lupiáñez and Rico (2008), Mucha, (2012), Ministry of Education (2007), Meza (2004) that support a .set of conditions necessary for carrying out an educational activity. With this, the following hypothesis is proposed: Reading images is significantly related to the . development of capacities in children of 5 years in the area of communication in the School No. 089 in the city of Rioja, 2015. Methodologically, the research design was descriptive and correlational with a sample of 24 children of School No. 089, and in the process of statistical analysis it was found that the central or research hypothesis is accepted with a 95% confidence, the same as is shown by the graph of Gauss curve and the value that was obtained from the Pearson correlation coefficient y s = o. 7138 it is a significant positive correlation.